China's new poetry or Into the mist - Lavrač, Maja (Azijske in afriške študije, 2010)
The late 1970s and early 1980s represent a period of important innovation in the development of contemporary Chinese poetry. As this was highly personal and experimental, it soon became characterized as being "misty" or "obscure". A new generation of young poets questioned the Chinese cultural tradition and expressed the need for its re-evaluation. They tried to re-examine the meaningof literature, and while doing so, they based the foundation for their poetry on the tradition and the spirit of personal freedom and democracy of the May 4th Movement (1919), having been at the same time strongly influenced by the Western modernist poetry, in which they found alternative fresh ideas.
Keywords: Bei, Dao; Gu, Cheng; Yang, Lian; kitajska književnost; kitajska poezija; literarne študije